La Fenomenología como realismo real - Aguirre-García, Juan Carlos (2020)
The aim of this paper is to explore Zahavi’s arguments for a Realistic Phenomenology. I claim that by relating Husserl and Putnam, Zahavi manages to formulate a Husserlian version of realism, which is, however, incapable of responding to the critiques from Speculative Realism. In order to this, I reconstruct the argument directed by Speculative Realism against Phenomenology of being Anti-realistic. Then, I present Zahavi’s response, and especially how he uses Putnam’s realism. Finally, I make some criticisms to Putnam’s view about Realism and argue that these criticisms can undermine the real realism with which Zahavi pretends to exonerate Husserl from Anti-realism.